2015
DOI: 10.1016/j.ijmst.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Potassium superoxide oxygen generation rate and carbon dioxide absorption rate in coal mine refuge chambers

Abstract: a b s t r a c tThe effects of the molding pressure of a KO 2 oxygen plate and the initial concentration of CO 2 on the oxygen generation rate, the oxygen generation efficiency, and the carbon dioxide absorption rate were studied using a YES-300 hydraulic press to alter the pressure when forming the oxygen plate used in a coal mine refuge chamber. In addition, changes in the initial concentration of CO 2 used in the closedbox model were made by adjusting the CO 2 supply system, and a CD-7 multi-function paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Alkali metal oxides (KO 2 , LiOH, and soda lime) have been widely used in adsorption for CO 2 in small- and medium-sized confined spaces in the case of electricity shortages or lacking space for a large adsorption bed. LiOH can ensure that the static adsorption rate reaches 75.6% and 80.8% in 24 h, but it produces dust and is hard to mold and to realize large-scale promotion of products due to its higher cost. , KO 2 was used by developing oxygen candles, which can achieve the supply of oxygen and the removal of CO 2 ; however, the reaction process is too fast and hard to control, not suitable for long-term CO 2 adsorption. , …”
Section: Introductionmentioning
confidence: 99%
“…Alkali metal oxides (KO 2 , LiOH, and soda lime) have been widely used in adsorption for CO 2 in small- and medium-sized confined spaces in the case of electricity shortages or lacking space for a large adsorption bed. LiOH can ensure that the static adsorption rate reaches 75.6% and 80.8% in 24 h, but it produces dust and is hard to mold and to realize large-scale promotion of products due to its higher cost. , KO 2 was used by developing oxygen candles, which can achieve the supply of oxygen and the removal of CO 2 ; however, the reaction process is too fast and hard to control, not suitable for long-term CO 2 adsorption. , …”
Section: Introductionmentioning
confidence: 99%
“…Jia et al (2014) investigated the performance of three materials, namely Ca(OH)2, LiOH, and NaOH, as CO2 absorbents, and the results indicated that the reaction rates of these three materials with CO2 gas from fast to slow were NaOH, LiOH, and Ca(OH)2. Gao et al (2015) investigated the application of KO2 to supply oxygen and remove CO2 gas. Their results demonstrated that, for a 15 g KO2 solid plate formed by pressure extrusion at 10 kN, the average oxygen production rate is 11.88 × 10 -3 L/min, while the average CO2 absorption rate is 11.0 × 10 -3 L/min.…”
Section: Relatively Stable Statementioning
confidence: 99%
“…These compounds are widely used by modern industry as bleaching materials, agents for air revitalization, sterilizing agents, and disinfectants. KO 2 is applied in spacecraft life support systems, which is a vital part of the air revitalization and control subsystems (ARCS) [3], self-contained breathing apparatus (SCBA), closed-circuit rebreathers (CCR) in space suits and life support systems (ECLSS), ranging from soviet spacecraft to self-contained selfrescuer devices for mine safety [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…KO 2 absorbs carbon dioxide and releases oxygen by reacting with the moisture of air [4]. As KO 2 performs multiple functions required in closed environments (humidity removal, oxygen provision, carbon dioxide removal) and its reactions are triggered by a metabolic waste product (respired moisture), it can be used as a base for a simple, passive, and compact air revitalization systems [5].…”
Section: Introductionmentioning
confidence: 99%